Persepsi Siswa Terhadap Pembelajaran Setelah Menggunakan Wordwall Kelas XI-V SMAN 1 Labuhan Haji - Farhana Muhammad; Nisa Iswandari; Siti Hadijah; Sahrul Jayadi; Yusril Iska Wandi; Rosmila (PADMA, 2026)
This qualitative study employed an intrinsic case study design to analyze the perceptions of grade XI-V students at SMA Negeri 1 Labuhan Haji regarding the use of the interactive learning medium Wordwall in Economics. The research aims to address the core problem in Economics classes, where students are often passive, sleepy, and find the subject boring due to its heavy theoretical nature. Data were collected through in-depth interviews (focusing on cognitive, affective, and conative dimensions of perception) and non-participant observation, and then analyzed using the interactive model by Miles, Huberman, and Saldaña. The results indicate a strong positive perception among the students. Wordwall proved successful in the affective dimension by creating a more engaging, enjoyable, and boredom-reducing learning environment. In the conative dimension, the medium enhanced student activeness, motivation, and concentration. The study concludes that Wordwall is an effective innovative solution for changing students' negative views toward learning Economics.